Argentina and Latin America under the rise of China and the Belt and Road initiative: Challenges and Proposals for a Constructive Integration - Merino, Gabriel Esteban (2023)
In LA, 21 countries have already joined the BRI. This advance in associativity and cooperation is in tune with China´s growing relevance in the region. The integration of Argentina and Latin America into the BRI and, in general, China´s intention to further deepen its ties with LA and Argentina, faces the challenge of being part of a shift in the patterns of integration that characterized this scenario since the formation of its national states and the deployment of British hegemony first and the more recently US hegemony. This requires both at the academic level and in the public policies field to orient actions that from the Argentinean / Latin American point of view procure: An Integration from autonomy, integration from the strengthening of the own macro-regional integrations, integration with/through industrialization, integration with technological development and strategic control of the industrialization process, macro integration from federal/local/sub-regional integration, and integration from/with the capacities of the State and the direction of the State.